Organizational methods for developing management creativity - Yousfi, Radhia (The International tax journal, 2025)
Today, promoting creativity and creative individuals has become an absolute necessity. It is an important tool for administrative leaders to address administrative challenges and problems. A creative individual is the true asset of any organization seeking to achieve effectiveness. Creativity is also a fundamental pillar for organizations seeking to develop and create new approaches to address various issues and problems. This is achieved by employing a creative approach and moving away from the traditional approach based on trial and error.